Analysis of maritime accident dynamics and risk factors: A focus on vessel age, human element, and safety trends in the Greek Merchant Fleet (2019–2023) (International Journal of Occupational Safety and Health, 2026)
Introduction: Maritime safety has evolved from reactive measures to proactive risk management. Despite the implementation of frameworks like the Formal Safety Assessment (FSA), maritime accidents continue to pose significant risks to occupational health and the environment. Recent global empirical studies, spanning from the South China Sea to North Atlantic shipping lanes, corroborate that these risks are not regionally isolated but represent a systemic challenge in modern seafaring. Unlike standard institutional reports (e.g., EMSA, ELSTAT) which primarily provide descriptive statistics, this study introduces an integrative analytical framework that correlates vessel age with specific human-machine interaction failures.Methods: By identifying a distinct 'risk threshold' at 20 years and proposing the 'reliability paradox' in automated systems, this research offers a methodological breakthrough in understanding how structural decay and technological dependency converge to influence maritime risk. The research employed a mixed-methods approach to correlate accident categories—such as collisions and hull failures—with vessel age and human-related causal factors.Results: The findings indicate that while incident frequency has risen, severity in terms of total ship losses has significantly decreased. The "human element" remains the primary catalyst, involved in approximately 75% of global incidents and 59.1% of the refined national study sample. A critical structural risk threshold was identified at 20 years of vessel age, beyond which the probability of hull failure and serious casualties indicates a sharp upward trend. Furthermore, a significant divergence in safety trends was observed, as the vast majority of recorded maritime fatalities occurred in coastal areas and were non-occupational, whereas occupational fatalities on commercial cargo ships and tankers remained remarkably low. The study proposes the emergence of a 'reliability paradox in mid-aged vessels (5–25 years), where increased reliance on advanced bridge automation is linked to higher collision risks due to diminished situational awareness.Conclusion: Enhancing maritime occupational safety requires a transition toward predictive analytics and AI-driven monitoring. Policy interventions should address the safety disparity between the commercial and fishing sectors and prioritize the optimization of human-machine interaction. This study underscores the need for targeted training to mitigate cognitive load and ensure the safety of the maritime profession in the digital age.